A low-temperature solder for photovoltaic welding strip of HJT heterojunction and preparation method thereof
By adding high-entropy alloy nanoparticles and flux to the tin-bismuth alloy, a low-temperature solder was developed, which solved the problem of thermal stress damage in high-temperature welding, achieved reliable interconnection under low-temperature conditions, improved welding quality and component life, and met environmental protection requirements.
Patent Information
- Application Number
- CN202411602384.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-11
AI Technical Summary
HJT battery cells are susceptible to thermal stress damage in traditional high-temperature welding processes, resulting in changes in the structure of amorphous silicon thin film, increasing carrier recombination, decreasing open circuit voltage and filling factor, and the high temperature accelerates the mutual diffusion between the metal electrode and the silicon material, forming an alloying layer, and increasing the contact resistance.
Using tin-bismuth alloy as the base material and adding high-entropy alloy nanoparticles and flux, a low-temperature solder was developed to achieve reliable interconnection of HJT cell and solder tape at temperatures below 250°C.
It significantly reduces the melting point of the solder, improves wettability, mechanical properties and corrosion resistance, improves welding quality and the service life of the components, and meets environmental protection requirements, avoids the use of toxic elements.
Smart Images

Figure CN119188022B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of packaging materials, and in particular, relates to a low-temperature solder for a photovoltaic soldering strip of a HJT heterojunction and a preparation method thereof. Background Art
[0002] With the continuous growth of global energy demand and the increasingly serious environmental problems caused by fossil fuels, renewable energy technology has received widespread attention from all over the world. Among them, photovoltaic power generation technology has become one of the most promising renewable energy technologies due to its advantages such as cleanliness, safety and reliability. The core of photovoltaic power generation technology is photovoltaic cells, among which silicon-based photovoltaic cells dominate the market. Traditional silicon-based photovoltaic cells mainly include monocrystalline silicon cells and polycrystalline silicon cells, but both of these cells have certain limitations in conversion efficiency and manufacturing cost. In order to further improve the conversion efficiency of photovoltaic cells and reduce manufacturing costs, researchers have developed various new photovoltaic cell technologies, such as thin-film cells, stacked cells, and perovskite cells. Among them, heterojunction (HJT) cells have attracted much attention due to their excellent performance. HJT cells refer to a cell structure in which a layer of amorphous silicon thin film is deposited on a monocrystalline silicon substrate to form a PN junction. Compared with traditional homojunction cells, HJT cells have the following advantages: High conversion efficiency: The maximum conversion efficiency of HJT cells can reach more than 26%, which is much higher than traditional monocrystalline silicon cells and polycrystalline silicon cells. Low temperature coefficient: The temperature coefficient of HJT cells is only -0.25% / ℃, while the temperature coefficient of traditional monocrystalline silicon cells is -0.45% / ℃, which means that the power generation of HJT cells decreases less in high temperature environments. Bifacial power generation: HJT cells can generate electricity on both the front and back of the cell, and the power generation is 20-30% higher than that of traditional cells. Simple process: The preparation process of HJT cells is relatively simple and the production cost is low. Although HJT cells have many advantages, they still face some challenges in practical applications, one of which is the interconnection problem between the cell and the welding ribbon. During the packaging process of photovoltaic modules, the cell needs to be interconnected with the welding ribbon to realize the collection and transmission of current. The traditional interconnection method is to use a high-temperature welding process, that is, to weld the welding ribbon to the metal electrode of the cell at a high temperature of 300-400℃. However, this high-temperature welding process will cause certain damage to the HJT cell, resulting in a decrease in the performance of the cell. Specifically, the thermal stress generated during high-temperature welding will cause changes in the structure of the amorphous silicon film in the HJT cell, resulting in increased carrier recombination and a decrease in the open circuit voltage and fill factor of the cell. In addition, high temperature will accelerate the mutual diffusion between the metal electrode and the silicon material in the cell, forming an alloy layer, increasing the contact resistance and reducing the current transmission efficiency.
[0003] In order to solve the above problems, researchers began to explore low-temperature interconnection technology, that is, to achieve reliable interconnection between battery cells and solder strips at a temperature below 250°C. Low-temperature interconnection technology can effectively reduce the damage of high temperature to HJT battery cells and improve the performance and reliability of battery cells. At present, low-temperature interconnection technologies mainly include the following: Conductive adhesive interconnection: Conductive adhesive is used to bond the solder strip to the metal electrode of the battery cell, and the conductive adhesive is solidified at low temperature to form a conductive path. The conductive adhesive interconnection technology has a simple process and low cost, but the conductivity and mechanical strength of the conductive adhesive are poor, and the long-term reliability needs to be improved. Ultrasonic welding: The high-frequency vibration of ultrasound is used to cold weld the solder strip to the metal electrode of the battery cell to form a metallurgical bond. Ultrasonic welding technology has high interconnection strength and low contact resistance, but it has high requirements for equipment and process parameters and is not easy to control. Laser welding: A high-energy-density laser beam is used to locally melt and metallurgically bond the solder strip to the metal electrode of the battery cell. Laser welding technology has a small heat-affected zone and high interconnection quality, but the equipment cost is high and there are also high requirements for the selection of welding materials. Low-temperature solder welding: Use low-melting-point solder to interconnect the solder strip and the cell at a temperature below 250°C. Low-temperature solder welding technology is simple, with good interconnection strength and conductivity, but it has high requirements on the performance of the solder, and special low-temperature solder needs to be developed.
[0004] In summary, low-temperature interconnection technology is one of the key technologies in HJT cell packaging, and is of great significance for improving the performance and reliability of HJT battery components. However, the existing low-temperature interconnection technology still has some shortcomings, such as the poor conductivity and reliability of conductive adhesive interconnection, the high equipment cost of ultrasonic welding and laser welding, and the high requirements for welding materials and process parameters. Although the traditional tin-Pb solder has a low melting point, it contains the highly toxic lead element. Therefore, the development of high-performance, low-cost, non-toxic and environmentally friendly low-temperature solder has become an important research direction in the field of HJT cell packaging. Summary of the invention
[0005] 1. Problems to be solved
[0006] HJT (heterojunction) cells have high conversion efficiency and low temperature coefficient, but the amorphous silicon film contained in its structure is very sensitive to high temperature. In the traditional high-temperature welding process, the welding temperature is usually between 300℃ and 400℃, which will cause the amorphous silicon film structure to change, increase the recombination rate of carriers, and thus reduce the open circuit voltage and fill factor of the cell. In addition, high temperature will accelerate the diffusion between the metal electrode and the silicon material, form an alloying layer, increase the contact resistance, and reduce the current transmission efficiency. In order to solve this problem, the present invention proposes a low-temperature solder, which can achieve reliable interconnection between the photovoltaic ribbon and the HJT cell at a temperature below 250℃, thereby effectively reducing the damage of high temperature to the performance of the cell. The performance of existing low-temperature solders is insufficient: Although some low-temperature solders are available on the market, they are insufficient in wettability, mechanical strength, corrosion resistance, etc. For example, although the common Sn-58Bi alloy has a low melting point (about 138℃), its mechanical strength and corrosion resistance are poor, and it is difficult to meet the long-term reliability requirements of HJT cell packaging. The present invention not only reduces the melting point of the solder, but also significantly improves its wettability, mechanical properties and corrosion resistance by adding high entropy alloy nanoparticles and flux to the tin-bismuth alloy, thereby improving the overall welding quality and the service life of the components. Although the traditional tin-lead solder has a low melting point, the lead element is toxic and poses a serious threat to the environment and human health. With increasingly stringent environmental regulations, lead-free environmentally friendly solder has become an important research direction in the photovoltaic industry. The present invention uses tin-bismuth alloy as the basic material, does not contain toxic elements such as lead, meets environmental protection requirements, and achieves both non-toxic environmental protection and high performance by optimizing the formula and preparation process, providing the photovoltaic industry with a green, safe and reliable new interconnection material. Some existing low-temperature interconnection technologies, such as conductive adhesive interconnection, ultrasonic welding and laser welding, can achieve interconnection at lower temperatures, but these technologies have certain limitations in terms of conductivity, mechanical strength or equipment cost. For example, although the conductive adhesive interconnection technology has a simple process, it has poor conductivity and mechanical strength; although the ultrasonic welding technology has high interconnection strength, the equipment cost is high and the process is complex. The present invention can mass-produce high-quality low-temperature solder by developing a simple and easy method for preparing low-temperature solder, and is suitable for existing photovoltaic module packaging production lines. This not only improves production efficiency, but also reduces production costs. In the photovoltaic module packaging process, the quality of solder joints directly affects the overall performance of the module. Traditional high-temperature welding processes are prone to problems such as cold joints and cold connections, and some existing low-temperature solders are also prone to similar problems due to poor wettability, thereby affecting the reliability of the module. The present invention improves the wettability of the solder by adding high-entropy alloy nanoparticles, so that it can achieve a good spreading effect at a lower temperature, thereby ensuring the quality and stability of the solder joints. In addition, the flux composition in the present invention is also optimized, which effectively reduces residues and improves cleanliness and production efficiency.Photovoltaic modules are exposed to outdoor environments for a long time and need to have good corrosion resistance to ensure their long-term stable operation. However, some existing low-temperature solders perform poorly in salt spray tests, which can easily shorten the life of the modules. In order to solve this problem, the present invention significantly improves the corrosion resistance of low-temperature solders by adding rare earth elements (such as cerium trioxide) and transition metals (such as ruthenium nitrate). Experimental data show that the relative corrosion area of the low-temperature solder prepared by the present invention in the salt spray test is much smaller than that of the comparative sample, indicating that it has better corrosion resistance and can effectively extend the service life of photovoltaic modules.
[0007] In summary, the present invention proposes a new low-temperature solder and its preparation method to solve the technical problems such as high temperature damage, poor wettability, insufficient mechanical strength, and weak corrosion resistance encountered in the HJT heterojunction photovoltaic cell packaging process. This invention not only solves the common problems in the prior art, but also provides the photovoltaic industry with an environmentally friendly, efficient, and reliable new interconnection material, which helps to promote the development and application of HJT heterojunction technology.
[0008] 2. Technical solution
[0009] To solve the above problems, the present invention adopts the following technical solutions.
[0010] A low-temperature solder for a photovoltaic ribbon of a HJT heterojunction, the low-temperature solder comprising the following components in percentage by weight:
[0011] 40%-60% tin;
[0012] 40%-60% bismuth;
[0013] 0.01%-1% high entropy alloy nanoparticles;
[0014] 0.5%-2% soldering flux, wherein the soldering flux is rosin-based soldering flux or organic acid soldering flux.
[0015] Preferably, the low temperature solder comprises the following components in weight percentage:
[0016] 50% tin;
[0017] 47.5% bismuth;
[0018] 0.8% high entropy alloy nanoparticles;
[0019] 1.7% soldering flux, wherein the soldering flux is rosin-based soldering flux or organic acid soldering flux.
[0020] Preferably, the preparation method of the high entropy alloy nanoparticles is as follows:
[0021] In an ice bath, add hexachloroplatinic acid, tetrachloropalladic acid, cobalt chloride, ferrous sulfate, cerium trioxide and ruthenium nitrate as metal precursors, the dosage of hexachloroplatinic acid, tetrachloropalladic acid, cobalt chloride, ferrous sulfate, cerium trioxide and ruthenium nitrate are all 20-30mM, then add 40-60mL of ultrapure water, stir and mix at 80rpm, add 5-10mL of 0.5-1M sodium borohydride, stir at 180rpm-220rpm for 5min, let stand for 40-80min, collect the product by centrifugation at 8000rpm, add 60-100mL of oleylamine, use a tubular furnace to calcine at 600-800℃ for 6-10h, wherein the heating rate is 10℃ / min, to obtain the product.
[0022] Preferably, the calcined material is washed with ultrapure water and then subjected to vacuum freeze drying.
[0023] Preferably, the rosin-based soldering flux is one of natural rosin, polymerized rosin and hydrogenated rosin.
[0024] Preferably, the organic acid soldering flux is one of lauric acid, phenylbutyric acid, phenylamidoacetic acid, citric acid, and 2,6-naphthalenesulfonic acid.
[0025] A method for preparing a low-temperature solder for a photovoltaic ribbon of a HJT heterojunction comprises the following steps:
[0026] Weigh tin, bismuth, high entropy alloy nanoparticles and flux according to weight percentage; add tin and bismuth into a crucible, heat to 280-300°C under nitrogen protection to melt, and stir evenly to form a tin-bismuth alloy melt; after the tin-bismuth alloy is completely melted, slowly add high entropy alloy nanoparticles, continue heating to maintain 280-300°C, and mechanically stir for 15-30 minutes to evenly distribute the high entropy alloy nanoparticles in the tin-bismuth alloy melt; then cool to 150°C, then cast into a solid alloy ingot, grind the solid alloy ingot into powder, add flux according to proportion, and evenly distribute the flux in the powder by mechanical mixing to obtain the product.
[0027] 3. Beneficial effects
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. Low melting point, suitable for low temperature interconnection process
[0030] Traditional high-temperature welding processes are usually carried out at temperatures above 300°C, which can cause serious thermal damage to HJT cells. In particular, the amorphous silicon thin film structure is prone to change at high temperatures, resulting in increased carrier recombination and reduced open circuit voltage and fill factor of the cell. In addition, high temperatures can also accelerate the diffusion between metal electrodes and silicon materials, forming an alloy layer and increasing contact resistance.
[0031] The present invention uses tin-bismuth alloy as the base material and adds high entropy alloy nanoparticles to significantly reduce the melting point of the solder. Experimental results show that the melting point of the low-temperature solder prepared by the present invention is between 88.9°C and 90.5°C, which is much lower than the 138°C melting point of common low-temperature solders on the market (such as Sn-58Bi). Therefore, the low-temperature solder of the present invention can achieve reliable interconnection between HJT cells and solder strips at a temperature below 250°C, effectively reducing the damage to the cells caused by high temperatures.
[0032] 2. Excellent wetting properties
[0033] Wettability is an important indicator to measure the ability of solder to spread on the surface of the material being welded. Good wettability can ensure a tight and uniform connection between the solder and the substrate, thereby improving the welding quality and efficiency. The present invention significantly improves the wettability of the solder by adding high entropy alloy nanoparticles. Experimental data show that the contact angle of the low-temperature solder prepared by the present invention is between 30.6° and 31.9°, which is significantly better than the comparative sample (36.5° to 38.0°). This means that the low-temperature solder of the present invention can achieve good wettability at a relatively low temperature, which helps to improve the interconnection quality during the HJT cell packaging process.
[0034] 3. Improve mechanical properties
[0035] The present invention not only reduces the melting point of the solder by adding high entropy alloy nanoparticles, but also significantly improves its mechanical properties. Experimental results show that the tensile strength of the low-temperature solder prepared by the present invention reaches 55.6MPa to 60.2MPa, and the elongation at break is 66.1% to 70.5%, which are significantly better than the comparative samples. This shows that the low-temperature solder of the present invention has high mechanical strength while maintaining good plasticity, can effectively cope with the mechanical stress that may occur during the packaging process of photovoltaic modules, and improves the reliability and service life of the modules.
[0036] 4. Excellent corrosion resistance
[0037] Photovoltaic modules are exposed to outdoor environments for a long time and need to have good corrosion resistance to ensure their long-term stable operation. The present invention significantly improves the corrosion resistance of low-temperature solder by adding rare earth elements (such as cerium trioxide) and transition metals (such as ruthenium nitrate). Experimental data show that the relative corrosion area of the low-temperature solder prepared by the present invention in the salt spray test is only 1.9% to 2.4%, which is much better than the comparative sample (5.8% to 14.9%). This shows that the present invention has better corrosion resistance and can effectively extend the service life of photovoltaic modules.
[0038] 5. Strong environmental protection
[0039] Although traditional tin-lead solder has a low melting point, the lead element is toxic and poses a serious threat to the environment and human health. With increasingly stringent environmental regulations, lead-free and environmentally friendly solder has become an important research direction in the photovoltaic industry. The present invention uses tin-bismuth alloy as the basic material, does not contain toxic elements such as lead, and meets environmental protection requirements. At the same time, the present invention achieves both non-toxicity and environmental protection and high performance by optimizing the formula and preparation process, providing the photovoltaic industry with a new type of green, safe and reliable interconnection material.
[0040] 6. The preparation process is simple and can be mass-produced
[0041] The present invention proposes a simple and easy method for preparing low-temperature solder. By optimizing the tin-bismuth alloy smelting process and the high-entropy alloy nanoparticle dispersion technology, high-quality low-temperature solder can be mass-produced. The specific steps include: heating and melting tin and bismuth, slowly adding high-entropy alloy nanoparticles, uniformly distributing them in the tin-bismuth alloy through mechanical stirring, then cooling them into solid ingots and grinding them into powder, and then adding flux and mixing them evenly to obtain the final product. The method is simple to operate, low in cost, and suitable for industrial production.
[0042] 7. Promote the development of photovoltaic technology
[0043] HJT heterojunction cells are considered to be an important development direction for the next generation of photovoltaic technology due to their high conversion efficiency, double-sided power generation, and simple process. However, their packaging process faces challenges brought by traditional high-temperature interconnection technology. The present invention provides a new interconnection solution for HJT cells by developing a special low-temperature solder and its preparation method, effectively solving the problem of high-temperature damage, improving component performance and reliability, and making an important contribution to promoting the development of photovoltaic technology.
[0044] In summary, the present invention has significant advantages over the prior art, including low melting point, high wettability, excellent mechanical properties, strong corrosion resistance, environmental protection and non-toxicity, and simple preparation process, etc. These beneficial effects make the present invention have broad application prospects in the field of HJT heterojunction photovoltaic module packaging, which helps to improve the overall performance of photovoltaic modules and promote the development of renewable energy technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a transmission electron microscope image of the high entropy alloy nanoparticles in Example 3.
[0046] Figure 2 This is the EDS element distribution diagram of the high entropy alloy nanoparticles in Example 3.
[0047] Figure 3 This is a DTA curve diagram of the low-temperature solder prepared in Example 3. DETAILED DESCRIPTION
[0048] The present invention is further described below in conjunction with specific embodiments.
[0049] Unless otherwise defined, technical and scientific terms used in the following examples have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.
[0050] Example 1
[0051] A low-temperature solder for a photovoltaic ribbon of a HJT heterojunction includes the following components in weight percentage:
[0052] 40% tin;
[0053] 57% bismuth;
[0054] 1% high entropy alloy nanoparticles;
[0055] 2% soldering flux, wherein the soldering flux is a rosin-based soldering flux.
[0056] The preparation method of the high entropy alloy nanoparticles is as follows:
[0057] In an ice bath, add hexachloroplatinic acid, tetrachloropalladic acid, cobalt chloride, ferrous sulfate, cerium trioxide and ruthenium nitrate as metal precursors. The dosage of hexachloroplatinic acid, tetrachloropalladic acid, cobalt chloride, ferrous sulfate, cerium trioxide and ruthenium nitrate is 20mM. Then add 60mL of ultrapure water, stir at 80rpm to mix, add 5mL of 1M sodium borohydride, stir at 180rpm for 5min, let stand for 80min, collect the product by centrifugation at 8000rpm, add 60mL of oleylamine, use a tubular furnace to calcine at 800℃ for 6h, and the heating rate is 10℃ / min. The calcined material is washed with ultrapure water and then freeze-dried in vacuum. The rosin-based flux is natural rosin with a density of 1.085g / cm 3 Its main component is resin acid, accounting for 92.7% of the total mass of rosin, and its molecular formula is C 20 H 30 O2. The organic acid soldering flux is lauric acid, and its molecular weight is 200.318 g / mol.
[0058] A method for preparing a low-temperature solder for a photovoltaic ribbon of a HJT heterojunction comprises the following steps:
[0059] Weigh tin, bismuth, high entropy alloy nanoparticles and flux according to weight percentage; add tin and bismuth into a crucible, heat to 280°C under nitrogen protection to melt, and stir evenly to form a tin-bismuth alloy melt; after the tin-bismuth alloy is completely melted, slowly add high entropy alloy nanoparticles, continue heating to maintain 300°C, and mechanically stir for 15 minutes to evenly distribute the high entropy alloy nanoparticles in the tin-bismuth alloy melt; then, cool to 150°C, and then cast into a solid alloy ingot, grind the solid alloy ingot into powder, add flux according to proportion, and evenly distribute the flux in the powder by mechanical mixing to obtain the product.
[0060] Example 2
[0061] A low-temperature solder for a photovoltaic ribbon of a HJT heterojunction includes the following components in weight percentage:
[0062] 60% tin;
[0063] 37% bismuth;
[0064] 1% high entropy alloy nanoparticles;
[0065] 2% soldering flux, wherein the soldering flux is a rosin-based soldering flux.
[0066] The preparation method of the high entropy alloy nanoparticles is as follows:
[0067] In an ice bath, add hexachloroplatinic acid, tetrachloropalladic acid, cobalt chloride, ferrous sulfate, cerium trioxide and ruthenium nitrate as metal precursors, the dosage of hexachloroplatinic acid, tetrachloropalladic acid, cobalt chloride, ferrous sulfate, cerium trioxide and ruthenium nitrate is 30mM, then add 40mL of ultrapure water, stir and mix at 80rpm, add 10mL of 0.5M sodium borohydride, stir at 220rpm for 5min, let stand for 40min, collect the product by centrifugation at 8000rpm, add 100mL of oleylamine, use a tubular furnace to calcine at 600℃ for 10h, wherein the heating rate is 10℃ / min, and the obtained product is obtained. The calcined material is washed with ultrapure water and then freeze-dried in vacuum. The rosin-based flux is hydrogenated rosin, CAS number: 65997-06-0, molecular weight: 304.47g / mol.
[0068] A method for preparing a low-temperature solder for a photovoltaic ribbon of a HJT heterojunction comprises the following steps:
[0069] Weigh tin, bismuth, high entropy alloy nanoparticles and flux according to weight percentage; add tin and bismuth into a crucible, heat to 300°C under nitrogen protection to melt, and stir evenly to form a tin-bismuth alloy melt; after the tin-bismuth alloy is completely melted, slowly add high entropy alloy nanoparticles, continue heating to maintain 280°C, and mechanically stir for 30 minutes to evenly distribute the high entropy alloy nanoparticles in the tin-bismuth alloy melt; then, cool to 150°C, and then cast into a solid alloy ingot, grind the solid alloy ingot into powder, add flux according to proportion, and evenly distribute the flux in the powder by mechanical mixing to obtain the product.
[0070] Example 3
[0071] A low-temperature solder for a photovoltaic ribbon of a HJT heterojunction includes the following components in weight percentage:
[0072] 50% tin;
[0073] 47.5% bismuth;
[0074] 0.8% high entropy alloy nanoparticles;
[0075] 1.7% soldering flux, wherein the soldering flux is an organic acid soldering flux.
[0076] The preparation method of the high entropy alloy nanoparticles is as follows:
[0077] In an ice bath, add hexachloroplatinic acid, tetrachloropalladic acid, cobalt chloride, ferrous sulfate, cerium trioxide and ruthenium nitrate as metal precursors, the dosage of hexachloroplatinic acid, tetrachloropalladic acid, cobalt chloride, ferrous sulfate, cerium trioxide and ruthenium nitrate are all 25mM, then add 50mL of ultrapure water, stir and mix at 80rpm, add 8mL of 0.8M sodium borohydride, stir at 200rpm for 5min, let stand for 70min, collect the product by centrifugation at 8000rpm, add 80mL of oleylamine, use a tubular furnace to calcine at 700℃ for 8h, where the heating rate is 10℃ / min, and obtain. The calcined material is washed with ultrapure water and then freeze-dried in vacuum. The organic acid flux is lauric acid, CAS number: 143-07-7.
[0078] A method for preparing a low-temperature solder for a photovoltaic ribbon of a HJT heterojunction comprises the following steps:
[0079] Weigh tin, bismuth, high entropy alloy nanoparticles and flux according to weight percentage; add tin and bismuth into a crucible, heat to 300°C under nitrogen protection to melt, and stir evenly to form a tin-bismuth alloy melt; after the tin-bismuth alloy is completely melted, slowly add high entropy alloy nanoparticles, continue heating to maintain 300°C, and mechanically stir for 25 minutes to evenly distribute the high entropy alloy nanoparticles in the tin-bismuth alloy melt; then, cool to 150°C, and then cast into a solid alloy ingot, grind the solid alloy ingot into powder, add flux according to proportion, and evenly distribute the flux in the powder by mechanical mixing to obtain the product.
[0080] Comparative Example 1
[0081] A low-temperature solder for a photovoltaic ribbon of a HJT heterojunction includes the following components in weight percentage:
[0082] 50% tin;
[0083] 47.5% bismuth;
[0084] 0.8% high entropy alloy nanoparticles;
[0085] 1.7% soldering flux, wherein the soldering flux is an organic acid soldering flux.
[0086] The preparation method of the high entropy alloy nanoparticles is as follows:
[0087] In an ice bath, add hexachloroplatinic acid, tetrachloropalladic acid, cobalt chloride, and ferrous sulfate as metal precursors, the dosage of hexachloroplatinic acid, tetrachloropalladic acid, cobalt chloride, and ferrous sulfate is 25mM, then add 50mL of ultrapure water, stir and mix at 80rpm, add 8mL of 0.8M sodium borohydride, stir at 200rpm for 5min, let stand for 70min, collect the product by centrifugation at 8000rpm, add 80mL of oleylamine, use a tubular furnace to calcine at 700℃ for 8h, where the heating rate is 10℃ / min, and obtain. The calcined material is washed with ultrapure water and then freeze-dried in vacuum. The organic acid flux is lauric acid, CAS number: 143-07-7.
[0088] A method for preparing a low-temperature solder for a photovoltaic ribbon of a HJT heterojunction comprises the following steps:
[0089] Weigh tin, bismuth, high entropy alloy nanoparticles and flux according to weight percentage; add tin and bismuth into a crucible, heat to 300°C under nitrogen protection to melt, and stir evenly to form a tin-bismuth alloy melt; after the tin-bismuth alloy is completely melted, slowly add high entropy alloy nanoparticles, continue heating to maintain 300°C, and mechanically stir for 25 minutes to evenly distribute the high entropy alloy nanoparticles in the tin-bismuth alloy melt; then, cool to 150°C, and then cast into a solid alloy ingot, grind the solid alloy ingot into powder, add flux according to proportion, and evenly distribute the flux in the powder by mechanical mixing to obtain the product.
[0090] Comparative Example 2
[0091] A low-temperature solder for a photovoltaic ribbon of a HJT heterojunction includes the following components in weight percentage:
[0092] 50% tin;
[0093] 47.5% bismuth;
[0094] 1.7% soldering flux, wherein the soldering flux is an organic acid soldering flux.
[0095] The organic acid soldering flux is lauric acid, CAS No.: 143-07-7.
[0096] A method for preparing a low-temperature solder for a photovoltaic ribbon of a HJT heterojunction comprises the following steps:
[0097] Weigh tin, bismuth and flux according to weight percentage; add tin and bismuth into a crucible, heat to 300°C for melting under nitrogen protection, and stir evenly to form a tin-bismuth alloy melt; then cool to 150°C and then cast into a solid alloy ingot, grind the solid alloy ingot into powder, add flux according to proportion, and evenly distribute the flux in the powder through mechanical mixing to obtain the product.
[0098] Test plan
[0099] (1) For the prepared high entropy alloy nanoparticles, take Example 3 as an example: Figure 1 As shown in the figure, it shows the transmission electron microscopy image of nanoparticles, which show that the nanoparticles are evenly distributed and there is no aggregation. Figure 2 As shown, it shows the EDS distribution diagram of six metal atoms inside the nanoparticles. It can be seen that the six metal atoms are distributed relatively evenly and can be well dispersed at various positions of the spherical nanoparticles.
[0100] (2) The low-temperature solders prepared in Examples 1-3 and Comparative Examples 1-2 were selected and their melting points were analyzed by differential thermal analysis (DTA).
[0101] Table 1 Melting point data table
[0102] Melting point(℃) Example 1 90.5 Example 2 89.7 Example 3 88.9 Comparative Example 1 104.1 Comparative Example 2 114.8
[0103] As shown in Table 1 and Figure 3 As shown, the low-temperature solder prepared in Example 3 of the best technical solution has a melting start temperature of 75.8°C and a melting point of 88.9°C. On the market, the melting points of common low-temperature solders are as follows: 281 (Bi-58Sn): Melting point: 138°C (eutectic point); 282 (Bi-57Sn-1Ag): melting point: 139°C; In-52Sn: melting point: 118°C; In-50Sn: solidus: 118°C, liquidus: 125°C; Sn-58Bi: melting point: 138°C; Sn-57Bi-1Ag: melting point: 140°C; pure indium (In): melting point: 157°C; In-97Ag: melting point: 143°C; In-99.3Ga: melting point: 152°C; In-99.4Ga: melting point: 153°C; In-99.6Ga: melting point: 154°C; In-80Pb-15Ag-5: solidus: 149°C, liquidus: 154°C. The melting points of these solders are higher than those of Examples 1-3 and Comparative Examples 1-2 of the present invention, and are not suitable for electronic packaging and connection processes that have strict temperature requirements, especially for the low-temperature welding requirements of HJT heterojunction photovoltaic cells.
[0104] (3) The wetting properties of low-temperature solder were evaluated by placing 10 mg of flux solder on a Cu substrate and reflowing it in a resistance furnace at 150 °C for 5 min.
[0105] Table 2 Wetting performance table
[0106] Contact angle (°) Example 1 31.9 Example 2 31.4 Example 3 30.6 Comparative Example 1 36.5 Comparative Example 2 38.0
[0107] It can be seen from Table 2 that the low-temperature solder prepared in Examples 1-3 of the present application has good wetting properties. The wettability of low-temperature solder refers to the ability of the solder to spread on the surface of the material to be welded and the wetting of the material to be welded. The better the wettability, the easier it is for the solder to form a tight and uniform connection with the material to be welded. Specifically, the better the wettability of the low-temperature solder, the following effects will occur: Better welding quality: Solders with good wettability can form a more uniform spreading area on the material to be welded, reduce pores and voids, and improve the integrity and reliability of the welded joint. Higher welding efficiency: Due to good wettability, the solder combines with the substrate faster, reducing welding time and improving production efficiency. Reduce welding stress: Good wettability means that the solder can achieve good connection at a lower temperature, reduce thermal stress caused by high temperature, and reduce thermal damage to the material during welding. Improve electrical performance: In electronic packaging and connection, solders with good wettability can ensure good electrical contact, reduce contact resistance, and improve the reliability of electronic equipment. Reduced residue: Solder with good wettability usually means that the amount of flux used can be reduced, resulting in less residue after welding, reducing the need for cleaning and pollution to the environment. Better mechanical properties: Due to the tighter bond between the solder and the material being welded, the welded joint has better mechanical strength and fatigue resistance. Lower defect rate: Good wettability can effectively reduce defects in welding, such as cold joints, cold joints, etc., and improve product reliability and consistency.
[0108] In addition, the contact angles of common low-temperature solders are as follows: In-Bi-Sn: contact angle: 35°; Sn-2.0Ag-0.5Cu-1.0Bi: contact angle: 35.6°; SAC105-2Sb-4.4In-0.3Bi: contact angle: 34.7°. These data show the wetting properties of different low-temperature solders under different conditions. The smaller the contact angle, the better the wettability. It is worth noting that the addition of nanoparticles (such as TiO2) or other elements (such as Ag, Cu, Bi) can significantly improve the wettability of low-temperature solders.
[0109] (4) Mechanical properties: Tensile tests were performed on the solder and copper / solder / copper joints at room temperature using a ZwickRoell Zwick Z010 at a strain rate of 1 mm / min.
[0110] Table 3 Mechanical properties
[0111] Tensile strength(MPa) Elongation at break (%) Example 1 55.6 66.1 Example 2 58.8 68.3 Example 3 60.2 70.5 Comparative Example 1 52.3 63.8 Comparative Example 2 48.9 58.2
[0112] As shown in Table 3, tensile strength analysis: Examples 1, 2, and 3: Example 3 has the highest tensile strength (60.2 MPa), followed by Example 2 (58.8 MPa) and Example 1 (55.6 MPa). This shows that the mechanical strength of the solder can be significantly improved by optimizing the solder formula and adding high entropy alloy nanoparticles. Comparative Examples 1 and 2: The tensile strengths of Comparative Examples 1 and 2 are relatively low, 52.3 MPa and 48.9 MPa, respectively, indicating that the mechanical properties of the solder without adding high entropy alloy nanoparticles or reducing key components are poor. Elongation at break analysis: Examples 1, 2, and 3: Example 3 has the highest elongation at break (70.5%), followed by Example 2 (68.3%) and Example 1 (66.1%). This shows that the addition of high entropy alloy nanoparticles not only improves the strength, but also improves the plasticity of the solder. Comparative Examples 1 and 2: The elongations at break of Comparative Examples 1 and 2 are 63.8% and 58.2%, respectively, which are significantly lower than the examples. This indicates that the plasticity of the solder decreases without the addition of high-entropy alloy nanoparticles.
[0113] (5) Corrosion resistance: According to ASTM B117 standard (5% NaCl at T = 35°C), the low-temperature solder was aged in a salt spray chamber for 9 h and aged at 45°C at standard salinity.
[0114] Table 4 Corrosion area
[0115] Corrosion relative area percentage (%) Example 1 2.4 Example 2 2.1 Example 3 1.9 Comparative Example 1 5.8 Comparative Example 2 14.9
[0116] As shown in Table 4, Examples 1, 2, and 3: In Examples 1, 2, and 3, the relative corrosion areas are all relatively low, indicating that these solders have good corrosion resistance. The corrosion area of Example 3 is the smallest (1.9%), indicating that its formula has the best corrosion resistance. Comparative Example 1 and Comparative Example 2: The corrosion areas of Comparative Example 1 and Comparative Example 2 are significantly larger, especially the corrosion area of Comparative Example 2 reaches 14.9%, indicating that after removing the high entropy alloy nanoparticles, the corrosion resistance of the solder is greatly reduced. Comparative Example 1 removes cerium trioxide and ruthenium nitrate, resulting in a decrease in its corrosion resistance, but it is still better than Comparative Example 2.
[0117] The present invention proposes a low-temperature solder for HJT heterojunction photovoltaic ribbon and a preparation method thereof. Its main features include:
[0118] Element:
[0119] -40%-60% tin
[0120] -40%-60% Bismuth
[0121] -0.01%-1% high entropy alloy nanoparticles
[0122] -0.5%-2% flux (rosin-based or organic acid)
[0123] Preparation method:
[0124] - Weigh the ingredients and melt tin and bismuth to form a tin-bismuth alloy melt.
[0125] -Slowly add high entropy alloy nanoparticles into the melt and stir mechanically to make it uniform.
[0126] - Cool to 150℃, cast into solid alloy ingot, grind into powder and add flux.
[0127] Preparation of high entropy alloy nanoparticles:
[0128] -Metal precursors such as hexachloroplatinic acid and tetrachloropalladium acid are added and prepared through steps such as ice bath, heating and mechanical stirring.
[0129] Technical effect:
[0130] - Low melting point: The melting point is in the range of 88.9℃ to 90.5℃, which is much lower than the melting point of traditional solders and is suitable for the low-temperature interconnection needs of HJT cells.
[0131] -Good wettability: The contact angle is between 30.6° and 31.9°, showing excellent wetting performance, ensuring welding quality and efficiency.
[0132] -Excellent mechanical properties: The tensile strength and elongation at break are higher than those of the comparative example, showing good mechanical strength and plasticity.
[0133] -Corrosion resistance: The relative area percentage of corrosion is low (1.9% to 2.4%), indicating that the solder has good corrosion resistance.
[0134] Environmental protection: It does not contain toxic elements such as lead and meets environmental protection requirements.
[0135] The low-temperature solder of the present invention solves the problem of high-temperature damage in HJT cell interconnection by optimizing the composition and preparation method, improves the welding quality, efficiency and reliability, and provides new interconnection materials and processes for the development of photovoltaic power generation technology. Comparative Example 1 removes cerium trioxide and ruthenium nitrate. From the perspective of high-entropy alloy nanomaterials, the change in solder performance can be attributed to the multiple mechanisms of metal atoms in high-entropy alloy nanoparticles on solder. Multi-element metal atom effect of high-entropy alloy nanoparticles: High-entropy alloy nanoparticles are composed of a variety of metal elements, such as platinum, palladium, cobalt, iron, cerium and ruthenium, and these metal atoms significantly improve the performance of solder through synergistic effects. After removing cerium trioxide (CeO2) and ruthenium nitrate (Ru(NO3)3), the key rare earth elements and transition metals are missing in the solder, resulting in the following performance changes: cerium trioxide and ruthenium nitrate reduce the melting point of the solder by forming a low melting point phase or changing the crystal structure in the high-entropy alloy. After removing these components, the melting point of the solder increased from 88.9°C to 104.1°C, indicating that these elements play an important role in lowering the melting point of the solder. Rare earth elements such as cerium have good surface activity, can reduce interfacial tension, and enhance the wettability of the solder to the substrate. After removing cerium trioxide, the wettability decreased significantly, and the contact angle of comparative example 1 increased from 30.6° to 36.5°. This shows that cerium plays a key role in improving wettability. Effect of metal atoms on mechanical properties: Various metal atoms in high entropy alloys improve the mechanical properties of solder through mechanisms such as solid solution strengthening and grain boundary strengthening. Specifically: rare earth elements (such as cerium) and transition metals (such as ruthenium) in high entropy alloys can improve the strength and ductility of the material by refining grains and inhibiting dislocation movement. After removing these elements, the tensile strength of comparative example 1 dropped from 60.2MPa to 52.3MPa, and the elongation at break also dropped from 70.5% to 63.8%. Corrosion resistance decreases: Rare earth elements such as cerium and transition metals such as ruthenium have good corrosion resistance. They can form a dense oxide layer on the surface of the material to prevent the intrusion of corrosive media. After removing cerium trioxide and ruthenium nitrate, the relative corrosion area of comparative example 1 increased to 5.8%, which is much higher than 1.9% in Example 3. This shows that these elements play an important role in improving corrosion resistance. After removing cerium trioxide and ruthenium nitrate, the multivariate synergistic effect of high entropy alloy nanoparticles in comparative example 1 was weakened, resulting in a significant decrease in the melting point, wettability, mechanical strength and corrosion resistance of the solder. These changes can be attributed to the important role of rare earth elements and transition metals in lowering the melting point, enhancing wettability, improving mechanical properties and improving corrosion resistance. Comparative Example 2 removes high entropy alloy nanoparticles, and the performance of the solder has changed significantly, mainly reflected in the increase in melting point, decrease in wettability, deterioration of mechanical properties and a significant decrease in corrosion resistance.In order to analyze the mechanism of these changes from the perspective of material dynamics and density functional theory (DFT) calculations, the mechanism of action of high-entropy alloy nanoparticles can be explored from the following aspects: Mechanism of increased melting point: High-entropy alloy nanoparticles can effectively reduce the melting point of solder through the synergistic effect of multiple metal atoms. According to DFT calculations, different metal atoms in high-entropy alloys have different electronic structures and bonding characteristics, which enable them to form stable low-melting phases. For example, the d orbital overlap bandwidth of elements such as Fe, Co, and Ni is large, which can form a strong coordination effect, thereby reducing the free energy and melting point of the overall system. When these high-entropy alloy nanoparticles are removed, this synergistic effect is missing in the solder, resulting in an increase in the melting point (from 88.9°C to 114.8°C). Mechanism of decreased wettability: High-entropy alloy nanoparticles not only play a role in reducing the melting point in the solder, but also improve the interfacial wettability between the solder and the substrate through their nanosize effect and multi-metal atomic distribution. At the nanoscale, high entropy alloy particles have a large specific surface area and good surface activity, which can significantly reduce the interfacial tension between the solder and the substrate, thereby improving wettability. In addition, rare earth elements (such as cerium) and transition metals (such as ruthenium) in high entropy alloys can also further enhance wettability through redox reactions. After removing these nanoparticles, the solder loses this interface regulation ability, resulting in poor wettability and an increase in the contact angle to 38.0°. Mechanism of mechanical property degradation: From the perspective of material dynamics, high entropy alloy nanoparticles significantly improve the mechanical properties of the solder through mechanisms such as solid solution strengthening and grain boundary strengthening. Due to their different atomic radii and lattice distortion effects, the various elements in high entropy alloys can effectively hinder dislocation movement, thereby improving the strength and ductility of the material. In addition, the twin deformation mechanism in high entropy alloys also helps to improve their plastic deformation ability, that is, under the combined action of dislocation slip and twin deformation, the material exhibits better strength and toughness. After removing the high-entropy alloy nanoparticles, these strengthening mechanisms were weakened, causing the tensile strength of the solder to drop from 52.3MPa to 48.9MPa, and the elongation at break to drop from 63.8% to 58.2%. Mechanism of decreased corrosion resistance: The multi-metal atoms in the high-entropy alloy effectively improve the corrosion resistance of the solder in a corrosive environment by forming a dense and stable oxide layer. For example, precious metal elements such as platinum and palladium have good antioxidant properties, while rare earth elements such as cerium can further enhance the corrosion resistance of the material by forming a self-healing oxide film36. When these high-entropy alloy nanoparticles are removed, the solder loses this multi-metal synergistic protection mechanism, resulting in a significant increase in its relative corrosion area to 14.9% in a salt spray environment. After removing the high-entropy alloy nanoparticles, the significant decrease in the performance of the solder in Comparative Example 2 can be attributed to the following aspects: DFT calculations show that the d orbital overlap and coordination effect of multi-metal atoms help to reduce the free energy of the solder system, thereby reducing the melting point.From the perspective of material dynamics, high entropy alloys significantly improve the mechanical properties of solders through solid solution strengthening, grain boundary strengthening, and twin deformation mechanisms. The noble metals and rare earth elements in high entropy alloys improve corrosion resistance by forming a stable oxide layer. Therefore, high entropy alloy nanoparticles play a key role in low-temperature solders, and their removal will significantly affect the performance of solders in many aspects.
[0136] The above contents are further detailed descriptions of the present invention in combination with specific implementation methods. It cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the field of packaging material technology to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope determined by the claims submitted for the present invention.
Claims
1. A low-temperature solder for photovoltaic ribbons of HJT heterojunctions, characterized in that: The low-temperature solder comprises the following components in weight percentage: 50% tin; 47.5% bismuth; 0.8% high entropy alloy nanoparticles; 1.7% solder flux, wherein the solder flux is a rosin-based solder flux or an organic acid solder flux; wherein the preparation method of the high entropy alloy nanoparticles is as follows: in an ice bath, adding hexachloroplatinic acid, tetrachloropalladic acid, cobalt chloride, ferrous sulfate, cerium trioxide and ruthenium nitrate as metal precursors, the amount of hexachloroplatinic acid, tetrachloropalladic acid, cobalt chloride, ferrous sulfate, cerium trioxide and ruthenium nitrate is 20-30mM, then adding ultrapure water for 4 0-60mL, stir at 80rpm to mix, add 5-10mL of 0.5-1M sodium borohydride, stir at 180rpm-220rpm for 5min, let stand for 40-80min, collect the product by centrifugation at 8000rpm, add 60-100mL of oleylamine, and calcine at 600-800℃ in a tubular furnace for 6-10h, wherein the heating rate is 10℃ / min, to obtain; wherein the calcined material is washed with ultrapure water and then freeze-dried in vacuum.
2. The low-temperature solder for photovoltaic ribbon of HJT heterojunction according to claim 1, characterized in that: The rosin-based soldering flux is one of natural rosin, polymerized rosin and hydrogenated rosin.
3. The low-temperature solder for photovoltaic ribbon of HJT heterojunction according to claim 2, characterized in that: The organic acid soldering flux is one of lauric acid, phenylbutyric acid, phenylamidoacetic acid, citric acid and 2,6-naphthalenesulfonic acid.
4. A method for preparing a low-temperature solder for a photovoltaic ribbon of a HJT heterojunction according to any one of claims 1 to 3, comprising the following steps: Weigh tin, bismuth, high entropy alloy nanoparticles and flux according to weight percentage; add tin and bismuth into a crucible, heat to 280-300°C under nitrogen protection to melt, and stir evenly to form a tin-bismuth alloy melt; after the tin-bismuth alloy is completely melted, slowly add high entropy alloy nanoparticles, continue heating to maintain 280-300°C, and mechanically stir for 15-30 minutes to evenly distribute the high entropy alloy nanoparticles in the tin-bismuth alloy melt; then cool to 150°C, then cast into a solid alloy ingot, grind the solid alloy ingot into powder, add flux according to proportion, and evenly distribute the flux in the powder by mechanical mixing to obtain the product.
Citation Information
Patent Citations
Tin-bismuth-based flux-cored wire and preparation method and application thereof
CN107552998A
Lead free solder compositions and manufacturing method of the same
KR102303704B1